2015
DOI: 10.1177/1362361315575840
|View full text |Cite
|
Sign up to set email alerts
|

Daily living skills in individuals with autism spectrum disorder from 2 to 21 years of age

Abstract: Daily living skills (DLS), such as personal hygiene, meal preparation, and money management, are important to independent living. Research suggests that many individuals with autism spectrum disorder exhibit impairments in daily living skills relative to their cognitive skills. This study examined predictors of daily living skills attainment and trajectories of daily living skills in a longitudinal sample referred for possible autism spectrum disorder and followed from 2 to 21 years of age. Consistent with pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
153
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 238 publications
(169 citation statements)
references
References 29 publications
12
153
1
3
Order By: Relevance
“…A lower DQ, the absence of functional speech, and increased CARS scores at inclusion predict a LG trajectory for communication, socialization, and daily living skills for most, but not all, participants. Other studies reported a similar relationship with IQ [Smith et al, ; Yang et al, ], autism severity [Yang et al, ], speaking ability [Szatmari et al, ], and nonverbal mental age [Bal, Kim, Cheong, & Lord, ]. In the absence of studies on long‐term effects of intervention, it is not possible to determine whether this poor outcome is intrinsic to a fraction of the autistic population, an effect of the absence of intervention, or limited exposure to learning opportunities.…”
Section: Discussionmentioning
confidence: 94%
“…A lower DQ, the absence of functional speech, and increased CARS scores at inclusion predict a LG trajectory for communication, socialization, and daily living skills for most, but not all, participants. Other studies reported a similar relationship with IQ [Smith et al, ; Yang et al, ], autism severity [Yang et al, ], speaking ability [Szatmari et al, ], and nonverbal mental age [Bal, Kim, Cheong, & Lord, ]. In the absence of studies on long‐term effects of intervention, it is not possible to determine whether this poor outcome is intrinsic to a fraction of the autistic population, an effect of the absence of intervention, or limited exposure to learning opportunities.…”
Section: Discussionmentioning
confidence: 94%
“…Mentored, parent-implemented structured teaching (MPST) intervention: Based on parent diaries and interviews completed, the hours of mentored, parent-structured teaching (MPST; a home program modeled after the TEACCH extended diagnostic services (Mesibov, Shea, & Schopler, 2005) from age 2 to 3 were computed. Consistent with analyses from previous studies (Anderson, Liang, & Lord, 2014;Bal, Kim, Cheong, & Lord, 2015) based on the median number of MPST hours (not including children with 0 h), hours of intervention were collapsed into two categories: (a) 'Minimal to None', that is, less than 20 hr; and (b) 'Some', that is, 20 hr or more between the 2-and 3-year-old assessments.…”
Section: Methodsmentioning
confidence: 99%
“…In ASD there is wide heterogeneity in the level of functioning across these domains, which is partly linked to development and level of cognitive abilities [Szatmari et al, ; Bal, Kim, Cheong, & Lord, ; Chatham et al, ; Farmer, Swineford, Swedo, & Thurm, ]. Although higher intellectual functioning is typically associated with better adaptive functioning, adaptive behavior tends to be more impaired than what would be expected based on general intellectual and cognitive ability [Bölte & Poustka, ; Klin et al, ; Charman et al, ; Kanne et al, ; Mouga, Almeida, Café, Duque, & Oliveira, ; Chatham et al, ].…”
Section: Introductionmentioning
confidence: 99%